Evaluation of Hemodynamics in Focal Steatosis and Focal Spared Lesion of the Liver Using Contrast-Enhanced Ultrasonography with Sonazoid - Kazue Shiozawa; Manabu Watanabe; Takashi Ikehara; Michio Kogame; Mie Shinohara; Masao Shinohara; Koji Ishii; Yoshinori Igarashi; Hiroyuki Makino; Yasukiyo Sumino (Radiology Research and Practice)
We aim to investigate the hemodynamics in focal steatosis and focal spared lesion of the liver using contrast-enhanced ultrasonography (CEUS) with Sonazoid. The subjects were 47 patients with focal steatosis and focal spared lesion. We evaluated enhancement patterns (hyperenhancement, isoenhancement, and hypoenhancement) in the vascular phase and the presence or absence of a hypoechoic area in the postvascular phase for these lesions using CEUS. Of the 24 patients with focal steatosis, the enhancement pattern was isoenhancement in 19 and hypoenhancement in 5. Hypoechoic areas were noted in the postvascular phase in 3 patients. Of the 23 patients with focal spared lesions, the enhancement pattern was isoenhancement in 18 and hyperenhancement in 5. No hypoechoic areas were noted in the postvascular phase in any patient. The hemodynamics in focal steatosis and focal spared lesions in nondiffuse fatty liver can be observed using low-invasive procedures in real-time by CEUS. It was suggested that differences in the dynamics of enhancement in the vascular phase of CEUS were influenced by the fat deposits in the target lesion, the surrounding liver parenchyma, and the third inflow.